Cooling of minichannel heat sink using nanofluids - Ijam, A.; Saidur, Rahman; Ganesan, P. (International Communications in Heat and Mass Transfer, 2012)
Nanofluids contain a small fraction of solid nanoparticles in base fluids. Nanofluids cooled small channel heat sinks, have been anticipated to be an excellent heat dissipation method for the next generation electronic devices. In this study, nanofluids are used with different volume fractions of nanoparticles as a coolant for the minichannel. Al2O3-water nanofluid and TiO2-water nanofluid were tested for the copper minichannel heat sink, with the bottom of 20 x 20 mm laminar flow as a coolant, through hydraulic diameters. The result showed that adding Al2O3 nanoparticles to water at 4 of volume fractions, enhanced the thermal conductivity by 11.98 and by dispersing TiO2 to the base fluid, was 9.97. It was found that using nanofluid such as Al2O3-water instead of water, improved the cooling by 2.95 to 17.32 and by using TiO2-water, 1.88 to 16.53 was achieved. The highest pumping power by using Al2O3-water and TiO2-water at 4 vol. and 0.1 m/s was 0.000552 W and at 4 vol. and 1.5 m/s was 0.12437 W.